Character Educational Content in the Origin of the Name of the Bandung City - Fajriani Ulfah Firdaus; Rahman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
This study aims to describe the values of character education in the folklore of the Origin of the Name of the City of Bandung. The method used is a qualitative descriptive method with research data sources in the form of a storybook of 78 Famous Legends of Indonesia published by Elex Media Computindo 2022 which contains 78 story titles. Data analysis is carried out using content analysis techniques. The results showed that folklore of the Origin of the City of Bandung as a literary work contains the value of character education which includes: (1) caring for others; (2) getting along well; (3) being wise; (4) hardwork; These values form the basis that folklore, in addition to being used as a medium to introduce stories that ancestors believe to be their descendants, can also be a means of educating their characters.